The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/eci.13530
|View full text |Cite
|
Sign up to set email alerts
|

Circulating pentraxin 3 in severe COVID‐19 or other pulmonary sepsis

Abstract: The plasma concentration of PTX3 was measured in 59 patients with severe COVID-19 and 59 propensity score-matched patients with other pulmonary sepsis enrolled in the ALBIOS trial. Circulating PTX3 was measured 1 ± 1 days and 7 ± 1 days after ICU admission for patients with COVID-19 or study entry, generally corresponding to the diagnosis of sepsis, for those in the ALBIOS trial. Results are presented as box plots where the boundary of the box closest to zero indicates the 25th percentile, the line within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…For example, a recent study has reported that long pentraxin 3 (PTX3) is an independent strong prognostic indicator for predicting mortality in COVID-19 and is a superior biomarker compared to conventional inflammatory markers [ 117 ]. Conversely, another study disputed this finding and has suggested that PTX3 is not any more valuable than other markers and that there are more important markers of inflammatory pathways [ 118 ]. Another study has reported that Growth Differentiation Factor 15 (GDF-15) is increased in patients who are hospitalized with COVID-19 and higher levels are associated with a worse outcome.…”
Section: The Potential Implications and Clinical Translation Of Senescence And Aging In Covid-19mentioning
confidence: 99%
“…For example, a recent study has reported that long pentraxin 3 (PTX3) is an independent strong prognostic indicator for predicting mortality in COVID-19 and is a superior biomarker compared to conventional inflammatory markers [ 117 ]. Conversely, another study disputed this finding and has suggested that PTX3 is not any more valuable than other markers and that there are more important markers of inflammatory pathways [ 118 ]. Another study has reported that Growth Differentiation Factor 15 (GDF-15) is increased in patients who are hospitalized with COVID-19 and higher levels are associated with a worse outcome.…”
Section: The Potential Implications and Clinical Translation Of Senescence And Aging In Covid-19mentioning
confidence: 99%
“…A relatively large biomarker study, including a total of 219 patients, measured PTX3 on a luminex assay-next to multiple other biomarkers-and also found a significant association with the primary endpoint of mortality regardless of whether patients were treated on a regular ward or in the intensive care unit (ICU) [58]. Since then, several smaller studies have further underlined the prognostic efficacy of PTX3 in COVID-19 [59][60][61][62].…”
Section: Pentraxin-3mentioning
confidence: 99%
“…It also works to activate the complement system against aspergillus by C3b binding, leading to alternate pathway activation. Aspergillus conidia, however, have mechanisms to evade complement activation including the masking of surface (1,3)-β-d-Glucan (BDG) and mannose by RodA, a surface hydrophobin, and through recruitment of complement inhibitors such as Aspf2 as well as the degradation of C3, C4 and C5 through protease secretion [ 46 , 47 ]. This critical role of pentraxan in preventing invasive aspergillosis is evident in pentraxan knock-out mice who were more susceptible to disease and showed clinical improvement upon its administration.…”
Section: Aspergillus In Health and Sars-cov-2mentioning
confidence: 99%
“…This critical role of pentraxan in preventing invasive aspergillosis is evident in pentraxan knock-out mice who were more susceptible to disease and showed clinical improvement upon its administration. Interestingly, serum pentraxan levels in ITU SARS-CoV-2 patients are unaffected versus those with sepsis from other pathogens, which may explain the heightened risk of CAPA in these patients [ 47 ]. Dendritic cells work as a link between activating the innate and adaptive immune response while also directly phagocytosing aspergillus and leading to further increase in proinflammatory cytokine release as well as an adaptive Th1-mediated response.…”
Section: Aspergillus In Health and Sars-cov-2mentioning
confidence: 99%